Design of an Electronic Test for Geometry Material Based on Students' Numeracy Literacy and Metacognitive Knowledge - Siska Firmasari; Setiyani; Jajo Firman Raharjo; Mohammad Dadan Sundawan; Rismayani (Universitas Pendidikan Ganesha, 2023)
Making electronic tests of students' numeracy skills based on metacognitive knowledge is important for students to have. Metacognitive knowledge are essential in mathematics performance. For this reason, it is significant to make metacognitive knowledge the basis of teaching, especially in teaching mathematics. This study aimed to design an electronic test based on students' Numerical Literacy Ability and Metacognitive Knowledge. The study used the ADDIE development model focusing on evaluating geometry material. This study chose subjects with random sampling from a high school that has good quality. The first stage of this study was to determine the nine research subjects by conducting initial interviews with class IX students. Then from the research subjects, researchers obtained information about numeracy literacy skills and metacognitive knowledge using test and interview methods. The results of a descriptive and in-depth analysis of the students' numeracy literacy skills and metacognitive knowledge became the basis for designing the electronic test. The study found that the electronic test design proved valid with an excellent category and practical with a positive response of 82.63%. This electronic-test design assessment shows that the digital-based instrument evaluation can have a broader range of users. The results of this study can be a recommendation for a digital-based evaluation instrument that adapts to the scope of the latest curriculum in Indonesia.